A multidisciplinary study for investigating the interaction of an iron complex with bovine liver catalase. (14th September 2022) - Hashemizadeh, Mojtaba; Shiri, Fereshteh; Shahraki, Somaye; Razmara, Zohreh
Abstract : Catalase (CAT) is an essential protein protecting the cell from oxidative damage by reactive oxygen species. CAT is a heme enzyme in which iron metal plays a crucial role in catalytic activity. In this research, an iron (II, III) complex ([Fe (bpy)3 ] [Fe (dipic)2 ]2 .7H2 O; dipic −2  = pyridine‐2, 6‐ dicarboxylato and bpy = 2, 2′‐bipyridine) was used to evaluate its binding interactions with bovine liver catalase (BLC) using spectroscopic and molecular docking methods. The experimental results demonstrated that the catalytic activity of BLC increased slightly and reached 106% of the initial activity. The interactions between Fe complex and BLC led to the quenching of the catalase fluorescence emission via the static quenching mechanism. Thermodynamic parameters demonstrated that the predominant interactions between catalase and Fe complex are hydrogen bond and van der Waals and the process is exothermic and enthalpy driven. The circular dichroism (CD) and synchronous fluorescence results showed that the Fe complex altered the structure and conformation of BLC. It changed the secondary structure of BLC by decreasing α‐helix and β‐sheet content. Also, the experimental data were analyzed using Multivariate Curve Resolution–Alternating Least Square (MCR‐ALS) to the resolution of measured complex spectra and estimate the number of independent chemical species. The docking results in agreement with experimental data showed that the cationic part of the complex with catalase is mainly hydrophobic and van der Waals interactions, and for the anionic part are hydrophobic, van der Waals, and hydrogen bonding. Abstract : The trinuclear iron (II, III) complex ([Fe (bpy)3 ] [Fe (dipic)2 ]2 .7H2 O interactions with bovine liver catalase (BLC) was studied. The conformational of β BLC structure was changed in the presence of Fe complexes. The interactions between BLC and Fe complex are hydrogen bond and van der Waals, and the process is exothermic and enthalpy driven.